Addressing the housing shortage: the case of India and South Africa - Bhandari, Shivani (2012)
This essay examines the Indian government’s efforts to respond to the issue of affordable housing in urban areas while identifying major impediments to successful delivery of the housing policy. It looks at South Africa’s experiences in combating affordable housing crisis and draws policy suggestions from it while utilizing census data, documentary review, information from government websites and articles form newspapers. Major obstacles to successful delivery of affordable housing include the scale and rapidity of urbanization, implementation problems and reluctance of state governments to embrace (the preached) institutional reforms. The study looks at pragmatic solutions and how they can be implemented in an effective manner in order to meet the needs of urban households living in informal settlements. Recognizing the role of private sector as instrumental in tackling the housing shortage successfully, a small survey of 200 participants (of the Lower Income Group (LIG)) from the city of Ahmedabad and an actionable plan to deliver affordable housing units has been formulated after taking into account policy suggestions from the study.